COVID and Working From Home - Bloom, Nicholas (2020)
ABSTRACT Working from home will be very much a part of our post-COVID economy. So the sooner policymakers and business leaders think of the implications of a home-based workforce, the better our firms and communities will be positioned when the pandemic subsides. Forty-two percent of U.S. workers are now working from home full time, accounting for more than two-thirds of economic activity. Policymakers should ensure that broadband service is expanded so more workers can do their jobs away from a traditional office. As companies consider relocating from densely populated urban centers in the wake of the COVID-19 crisis, cities may suffer while suburbs and rural areas benefit. Working from home is here to stay, but post-pandemic will be optimal at about two days a week. Keywords Working from home, economics policy, infrastructure planning ABOUT THE AUTHOR/S Nicholas Bloom Stanford University nbloom@stanford.edu Nicholas (Nick) Bloom is the William Eberle Professor of Economics at Stanford University, a Senior Fellow of SIEPR, and the Co-Director of the Productivity, Innovation and Entrepreneurship program at the National Bureau of Economic Research. His research focuses on management practices and uncertainty. He previously worked at the UK Treasury and McKinsey & Company. He is a Fellow of the American Academy of Arts and Sciences, and the recipient of the Alfred Sloan Fellowship, the Bernacer Prize, the European Investment Bank Prize, the Frisch Medal, the Kauffman Medal and a National Science Foundation Career Award. He has a BA from Cambridge, an MPhil from Oxford, and a PhD from University College London. On the personal side he is English, living with his Scottish wife and American kids on Stanford campus, in a multi-lingual English household. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).